Sea‐turtle observations at Matura Beach, Trinidad, using thermal UAS imagery: A strategy to support monitoring and conservation efforts - Adrian Wilson; Deanesh Ramsewak; Kyle Mitchell; Cassandra Ali; Arvind Jagassar; Brendan Mastay; Suzan Lakhan‐Baptiste (Wildlife Society Bulletin)
Abstract The use of drones in wildlife monitoring and conservation efforts can offer remarkable advantages over traditional in situ monitoring techniques. Trinidad and Tobago is a twin‐island state situated at the southeastern end of the Lesser Antilles, which supports approximately 80% of the leatherback turtle (Dermochelys coriacea) population in the Caribbean. Leatherback turtles nest in various areas along the coast of the northeast section of the island of Trinidad, with the Matura Beach region having an active turtle nesting population during March‐August each year. In recent years, sea turtle monitoring and conservation efforts on Matura Beach have been impacted by a lack of funding and, consequently, human resources for adequate patrols. Our study leveraged the performance of a drone with a Thermal Infrared (TIR) camera and long flight capability in windy coastal regions as a technological support tool to aid in sea turtle monitoring and conservation efforts. The drone was used for identifying leatherback turtles during the nesting period and patrolling remote regions of the study area. A series of metrics, including morphological features, heat signatures, and turtle track formation, were assembled to effectively identify turtles from the drone imagery. Our study showed positive results for the use of drones in turtle species identification. We recorded 394 leatherback turtles across 52 flight nights and successfully reallocated patrol efforts to areas along the beach where nesting densities were higher on a nightly basis. As a result, drone monitoring will be incorporated into monitoring protocols moving forward. Weather conditions and image quality were limitations within this study and should be considered in other cases. Overall, drones can play a useful role in sea turtle conservation by providing aerial support for locating nesting sites and facilitating more efficient, targeted conservation efforts.